The role of 18F-FDG PET/CT in patients with synchronous multiple primary malignant neoplasms occurring at the same time - Luo, Zhe Huang; Qi, Wan Ling; Jin, Ai Fang; Liao, Feng Xiang; Liu, Qian; Zeng, Qing Yun (Frontiers in Oncology, 2022)
Background Synchronous multiple primary malignant neoplasms occurring at the same time (SMPMNS) are not currently uncommon in clinical oncological practice; however, the diagnostic performance of 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) for SMPMNS needs further elucidation. Purpose This study aimed to evaluate the application of 18F-FDG PET/CT in patients with SMPMNS. Materials and methods The clinical and imaging data of 37 patients with SMPMNS who had undergone 18F-FDG PET/CT from October 2010 to December 2020 were retrospectively analyzed. The kappa consistency test was applied to evaluate the consistency of the diagnostic performance between PET/CT and conventional imaging (CI). The sensitivity, specificity, and accuracy of PET/CT and CI in the detection of metastatic lesions were compared. Results This retrospective diagnostic study included 74 lesions identified in 37 patients with SMPMNS, with 94.6% of patients having double primary tumors. Of the incidences of SMPMNS, 18.9% occurred in the same organ system, with respiratory tumors being the most common type of neoplasm (43.2%) and the lung being the most common primary site (40.5%). The overall survival of SMPMNS patients without metastases was longer than that of those with metastases (χ2 = 12.627, p = 0.000). The maximum standardized uptake value (SUVmax), the SUVmax ratio (larger SUVmax/smaller SUVmax), and the difference index of SUVmax (DISUVmax) [(larger SUVmax − smaller SUVmax)/larger SUVmax] of the primary lesions ranged from 0.9 to 41.7 (average = 12.3 ± 7.9), from 0.3 to 26.7 (average = 4.4 ± 6.9), and from 0.0% to 96.3% (average = 50.3% ± 29.3%), respectively. With regard to diagnostic accuracy, PET/CT and CI showed poor consistency (κ = 0.096, p = 0.173). For the diagnosis of primary lesions (diagnosed and misdiagnosed), PET/CT and CI also showed poor consistency (κ = 0.277, p = 0.000), but the diagnostic performance of PET/CT was better than that of CI. In the diagnosis of metastases, the patient-based sensitivity, specificity, and accuracy of PET/CT were 100.0%, 81.8%, and 89.2%, respectively, while those of CI were 73.3%, 100.0%, 89.2%, respectively. The sensitivity and specificity values were significantly different, with PET/CT having higher sensitivity (p = 0.02) and CI showing higher specificity (p = 0.02). Conclusions 18F-FDG PET/CT improves the diagnostic performance for SMPMNS and is a good imaging modality for patients with SMPMNS.